THE APPLICATION OF BIBLIOTHERAPY THROUGH WATTPAD IN ISLAMIC-BASED COGNITIVE COUNSELING SERVICE TO MAINTAIN MENTAL HEALTH - KHILMAN ROFI’AZMI; MELLIA IRAWATI (Universitas Islam Negeri Mataram, 2022)
There are several approaches to changing a person's behavior such as using the media of Bibliotherapy. Bibliotherapy is a medium that defines the use of literature and poetry to treat people with ego and mental illnesses. This study aims to determine students' understanding of mental health and the effectiveness of students using the Wattpad media. The approach used is Research and Development (R&D). data collection tool using questionnaires, observations and documentation. From the results of the study, it can be concluded that the use of Bibliotherapy using